Clastic sedimentary records of the Upper Triassic Sichuan Basin, China: Implications for the transition from marine to transitional environment. Issue 11 (21st August 2022) - Shi, Zhensheng; Zhou, Tianqi; Guo, Changmin
Abstract : The Upper Triassic Xiaotangzi and Xujiahe formations are important gas exploration targets in the Sichuan Basin. This article, based on a systematic analysis of sandstone clastic framework components, depositional structures, clay minerals, trace elements and organic geochemistry, gives a detailed discussion regarding their sedimentary environment. There exist abundant tide‐generated depositional structures in this sequence, and the sedimentary provenance was dominated by a recycled orogen belt in the north and by a continental block at an early stage then recycled orogen belt at the late stage in the south of the western Sichuan Basin. The Xiaotangzi Formation and members 2–3 of the Xujiahe Formation only have authigenic illite and chlorite. In contrast, members 4–6 contain increasing kaolinite and decreasing illite and chlorite from bottom to top. The water column salinity gradually downgraded from hyperhaline, euhaline and polyhaline of the Xiaotangzi Formation to member 2 to polyhaline and mesohaline of members 3–6. The source rocks of the Xiaotangzi and Xujiahe formations have a generally low Pr/Ph, minus the value of (Pr/nC17 )‐(Ph/nC18 ), and high values of Pr/nC17 and Ph/nC18 . They also show apparent dominance of 9‐MP in methylphenanthrene composition and different point groups of fluorenes, dibenzofurans and dibenzothiophenes from marine or salt lake facies, as well as typical swamp facies. In conclusion, the Xiaotangzi Formation and members 2–3 were deposited in a marine environment, whereas members 4–6 were deposited mainly in a transitional to the continental environment. Abstract : Based on a systematic analysis of sandstone clastic framework components, depositional structures, clay minerals, trace elements and organic geochemistry, the paper gives detailed evidence of the depositional environment transition of the marine environment to the continental environment during the sedimentation period of the Xujiahe Formation.